Academic deficiency in first year medicine students - Ángel García Gascón; Marlene Gorguet Pi; Elio Cisneros Prego; Julio César Chi Rivas (Centro Provincial de Información de Ciencias Médicas, 2019)
Introduction: The academic performance can be conceptualized as the level of instructions achieved by the students, in which the systemic correlation with the professor has a basic role. Objective: To determine some psychosocial aspects associated with the poor academic performance in students. Methods: A descriptive and cross-sectional study of 285 first year medicine students, belonging to the Medicine Faculty No. 2 of the University of Medical Sciences was carried out during 2017 in Santiago de Cuba who had failed the subject Nervous, Endocrine and Reproductive Systems. A survey, Holmes and Rahe estress scale, the feature-state anxiety and Beck depression inventories were carried out; the frequent and partial evaluations marks, the intrasemestral exam and the student's trajectory in the subject were also taken into account. Results: In the series a prevalence of the poor academic perfomance was obtained in females and inadequate lifestyles and divorce of the parents were among the most frequent social factors, while among the psychological factors we can mention the lack of motivation and high estress levels.